Post-exertion oxygen saturation as a prognostic factor for adverse outcome in patients attending the emergency department with suspected COVID-19: a substudy of the PRIEST observational cohort study. Issue 2 (3rd December 2020) - Goodacre, Steve; Thomas, Ben; Lee, Ellen; Sutton, Laura; Loban, Amanda; Waterhouse, Simon; Simmonds, Richard; Biggs, Katie; Marincowitz, Carl; Schutter, José; Connelly, Sarah; Sheldon, Elena; et al.
Abstract : Background: Measurement of post-exertion oxygen saturation has been proposed to assess illness severity in suspected COVID-19 infection. We aimed to determine the accuracy of post-exertional oxygen saturation for predicting adverse outcome in suspected COVID-19. Methods: We undertook a substudy of an observational cohort study across 70 emergency departments during the first wave of the COVID-19 pandemic in the UK. We collected data prospectively, using a standardised assessment form, and retrospectively, using hospital records, from patients with suspected COVID-19, and reviewed hospital records at 30 days for adverse outcome (death or receiving organ support). Patients with post-exertion oxygen saturation recorded were selected for this analysis. We constructed receiver-operating characteristic curves, calculated diagnostic parameters, and developed a multivariable model for predicting adverse outcome. Results: We analysed data from 817 patients with post-exertion oxygen saturation recorded after excluding 54 in whom measurement appeared unfeasible. The c-statistic for post-exertion change in oxygen saturation was 0.589 (95% CI 0.465 to 0.713), and the positive and negative likelihood ratios of a 3% or more desaturation were, respectively, 1.78 (1.25 to 2.53) and 0.67 (0.46 to 0.98). Multivariable analysis showed that post-exertion oxygen saturation was not a significant predictor of adverse outcome when baseline clinical assessment was taken into account (p=0.368). Secondary analysis excluding patients in whom post-exertion measurement appeared inappropriate resulted in a c-statistic of 0.699 (0.581 to 0.817), likelihood ratios of 1.98 (1.26 to 3.10) and 0.61 (0.35 to 1.07), and some evidence of additional prognostic value on multivariable analysis (p=0.019). Conclusions: Post-exertion oxygen saturation provides modest prognostic information in the assessment of selected patients attending the emergency department with suspected COVID-19. Trial registration number: ISRCTN Registry (ISRCTN56149622 ) http://www.isrctn.com/ISRCTN28342533 .